Central venous catheter‐related thrombosis and thromboprophylaxis in children: a systematic review and meta‐analysis. (19th June 2014) - Vidal, E.; Sharathkumar, A.; Glover, J.; Faustino, E. V. S.
Summary Objectives In preparation for a pediatric randomized controlled trial on thromboprophylaxis, we determined the frequency of catheter‐related thrombosis in children. We also systematically reviewed the pediatric trials on thromboprophylaxis to evaluate its efficacy and to identify possible pitfalls in the conduct of these trials. Patients/Methods We searched MEDLINE, EMBASE, Web of Science and the Cochrane Central Register for Controlled Trials for articles published until December 2013. We included cohort studies and trials on patients aged 0–18 years with central venous catheters who underwent active surveillance for thrombosis with radiologic imaging. We estimated the pooled frequency of thrombosis and the pooled risk ratio (RR) with thromboprophylaxis by using a random effects model. Results From 2651 articles identified, we analyzed 37 articles with 3128 patients. The pooled frequency of thrombosis was 0.20 (95% confidence interval [CI] 0.16–0.24). In 10 trials, we did not find evidence that heparin‐bonded catheters (RR 0.34; 95%CI 0.01–7.68), unfractionated heparin (RR 0.93; 95% CI 0.57–1.51), low molecular weight heparin (RR 1.13; 95% CI 0.51–2.50), warfarin (RR 0.85; 95%CI 0.34–2.17), antithrombin concentrate (RR 0.76; 95% CI 0.38–1.55) or nitroglycerin (RR 1.53; 95%CI 0.57–4.10) reduced the risk of thrombosis. Most of the trials were either not powered for thrombosis or were powered to detect large, probably unachievable, reductions in thrombosis. Missing data on thrombosis also limited these trials. Conclusions Catheter‐related thrombosis is common in children. An adequately powered multicenter trial that can detect a modest, clinically significant reduction in thrombosis is critically needed. Missing outcome data should be minimized in this trial.